Presenting a Model for Managing Teachers' Professional Growth with a Meta-analyze Approach - Rezaei, Jabar; Jafari, Sepideh; Omidian, Farank (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The primary goal of this research was to present a model for managing teachers' professional growth using a meta-analyze approach.Method: This study was classified as applied research in terms of its objective and qualitative in terms of the nature of its data and analysis style, employing a meta-analyze method. The method of data collection in this research was based on documentary information. Research data were collected and analyzed using a meta-analyze approach to gather data related to the study, which involved all studies conducted in the field of teachers' professional growth, and then the effective components in these studies were identified and extracted using the seven-step method of Sandelowski and Barroso (2007).Findings: The findings indicated that the model for managing teachers' professional growth comprises 124 indicators and 10 main dimensions including: Education, Educational Technologies, Skill Development, Learning and Knowledge Transfer, Educational Leadership, Interaction and Collaboration, Individual Factors, Organizational Factors, Professional Growth Strategies, and Evaluation and Feedback.Conclusion: Based on the results, it can be said that teachers' growth has various dimensions, thus, educational system planners can pay attention to these dimensions and act towards enhancing and better managing teachers' growth.